2023
DOI: 10.1002/jat.4447
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic acid ameliorates lipopolysaccharide‐induced kidney damage in mice via downregulation of TLR‐4‐mediated IKBKB/NF‐κB and MAPK/Erk signaling pathways

Abstract: Acute kidney injury (AKI) is a very critical cause of death in the whole world. Lipopolysaccharide (LPS) induces kidney damage by activating various deleterious inflammatory and oxidative pathways. Protocatechuic acid, a natural phenolic compound, has shown to exert beneficial effects against oxidative and inflammatory responses.The study aimed to clarify the nephroprotective activity of protocatechuic acid in LPS-induced acute kidney damage in mice. Forty male Swiss mice were allocated in four groups as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have shown that ingredients such as caffeic acid, protocatechuic acid, gallic acid, bilobalide, and ginkgolide A can inhibit the TLR4/NF-κB signalling pathway, reduce the expression level of MAPK, and achieve anti-inflammatory effects. 23,25,29,31,33 Bilobalide, ginkgolide A, and so on can play an antiinflammatory role by regulating inflammation-related pathways and inhibiting the release of inflammatory factors. Quercetin-3-O-rutinoside, kaempferol-3-O-rutinoside, kaempferol-3-O-glucoside, and isorhamnetin-3-O-rutinoside can inhibit the PI3K-Akt, NF-κB, and other signalling pathways and reduce cardiovascular and cerebrovascular injuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations